2019
DOI: 10.1037/cdp0000254
|View full text |Cite
|
Sign up to set email alerts
|

“Never give up. Fight for what you believe in”: Perceptions of how Latina/o adolescents can make a difference.

Abstract: Objective: Latina/o adolescents have been described as less likely to participate in volunteer and civic activities relative to other youth. The present study elicited Latina/o youths' own views of how they can make a difference in their communities. Method: Latina/o high school students (N ϭ 686; one third males; M age ϭ 16.3, SD ϭ 1.2) responded in writing to the open-ended question, "How do you think that Latina and Latino young people can make a difference in our communities?" Data were analyzed using them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Others have used qualitative methods to better understand how critical consciousness manifests by examining the perspectives of youth. For example, in a recent qualitative study exploring the perceptions of Latinx youth about what they can do to make a difference in their communities, McWhirter, Gomez, and Rau (2019) found that responses from youth were aligned with themes related to sociopolitical development and critical consciousness, including speaking out to address injustice, fighting against racism and discrimination, and fighting for equality, among others. The authors characterized participant responses and related themes as manifestations of critical consciousness, specifically in terms of critical reflection, critical agency, and critical action.…”
Section: How Has Critical Consciousness Been Measured?mentioning
confidence: 99%
“…Others have used qualitative methods to better understand how critical consciousness manifests by examining the perspectives of youth. For example, in a recent qualitative study exploring the perceptions of Latinx youth about what they can do to make a difference in their communities, McWhirter, Gomez, and Rau (2019) found that responses from youth were aligned with themes related to sociopolitical development and critical consciousness, including speaking out to address injustice, fighting against racism and discrimination, and fighting for equality, among others. The authors characterized participant responses and related themes as manifestations of critical consciousness, specifically in terms of critical reflection, critical agency, and critical action.…”
Section: How Has Critical Consciousness Been Measured?mentioning
confidence: 99%
“…Latinx youth's sense of agency may also take collective forms. McWhirter et al (2019) elicited high school Latinx youth's voices through the administration of an open-ended question by asking youth how they believed Latinx young people could make a difference in their communities. Findings indicated that youth believed that Latinx youth could engage in their communities through community efforts that support others which may include others in the Latinx community, advocacy that involved speaking out, fighting for equality and against racism, taking pride in their culture, heritage, and language, challenging stereotypes about Latinx people, and pursuing education that advance their own and families lives and the larger Latinx community.…”
Section: A Sense Of Emancipatory Agency and Commitment To End Racismmentioning
confidence: 99%
“…Given foundational questions about the ways in which marginalized people develop sociopolitical processes about issues that negatively impact their lives (Freire, 1974), resulting developmental theory and research has primarily focused on Black, primarily African American, youth’s development of these processes (Anyiwo et al., 2021; Hope et al., 2020). However, there is emerging research focusing on Latinx youth and young adults (Bañales, Mathews, et al., 2019; Constante et al., 2021; Diemer & Rapa, 2016; McWhirter & McWhirter, 2016; McWhirter et al., 2019; Pinedo et al., 2021) and youth of color broadly (e.g., Anyiwo et al., 2020; Mathews et al., 2020). Despite these advancements, there is limited theoretical and empirical work that deconstructs within‐group differences in Latinx youth’s critical consciousness development, especially critical racial consciousness.…”
Section: Critical Analysis Of Racism: a Key Ingredientmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being perceived as less likely to participate in civic engagement than their peers, Latinx youth report a variety of ways they can make a difference in their communities, including engagement with communities, advocacy, maintaining cultural pride, and educational persistence (McWhirter et al., 2019). Experiences of discrimination have predicted critical action (Tyler et al., 2020), suggesting youth are motivated to dismantle oppression.…”
Section: Dismantling Oppressive Systems Of Discriminationmentioning
confidence: 99%